Human Milk Oligosaccharides: Their Effects on the Host and Their Potential as Therapeutic Agents - Rousseaux, Anaïs; Brosseau, Carole; Le Gall, Sophie; Piloquet, Hugues; Barbarot, Sébastien; Bodinier, Marie (Frontiers in Immunology, 2021)
Breastmilk is known to be very important for infants because it provides nutrients and immunological compounds. Among these compounds, human milk oligosaccharides (HMOs) represent the third most important component of breastmilk after lipids and lactose. Several experiments demonstrated the beneficial effects of these components on the microbiota, the immune system and epithelial barriers, which are three major biological systems. Indeed, HMOs induce bacterial colonization in the intestinal tract, which is beneficial for health. The gut bacteria can act directly and indirectly on the immune system by stimulating innate immunity and controlling inflammatory reactions and by inducing an adaptive immune response and a tolerogenic environment. In parallel, HMOs directly strengthen the intestinal epithelial barrier, protecting the host against pathogens. Here, we review the molecular mechanisms of HMOs in these different compartments and highlight their potential use as new therapeutic agents, especially in allergy prevention.